PERAN BAHAN AJAR IPAS BERBASIS BUDAYA DAN KEARIFAN LOKAL DALAM MENINGKATKAN LITERASI SISWA SEKOLAH DASAR - Dian Shofariatu Laeli; Ardhi Prabowo; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of Natural and Social Sciences (IPAS) teaching materials based on culture and local wisdom in South Sumatra in improving elementary school students' literacy. The study used a qualitative approach with a literature study method on various existing scientific publications. Data were obtained from accredited journals, proceedings, and relevant scientific articles, then analyzed using content analysis techniques. The results of the study indicate that local wisdom-based teaching materials can increase students' interest in reading, comprehension of reading content, and critical thinking skills. In addition, contextual teaching materials also increase student engagement and help connect learning materials to real life. In the context of South Sumatra, the utilization of local cultural potential such as traditions, river environments, and community social systems has proven relevant as a learning resource. However, the use of local wisdom in teaching materials is still not optimal in some schools. Therefore, the development of culture- and local wisdom-based teaching materials needs to be continuously improved as an effective and contextual learning strategy to improve elementary school students' literacy. Penelitian ini bertujuan untuk menganalisis peran bahan ajar Ilmu Pengetahuan Alam dan Sosial (IPAS) berbasis budaya dan kearifan lokal Sumatera Selatan dalam meningkatkan literasi siswa sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan metode studi literatur terhadap berbagai publikasi ilmiah yang ada. Data diperoleh dari jurnal terakreditasi, prosiding, dan artikel ilmiah yang relevan, kemudian dianalisis menggunakan teknik analisis isi. Hasil kajian menunjukkan bahwa bahan ajar berbasis kearifan lokal mampu meningkatkan minat baca, pemahaman isi bacaan, serta kemampuan berpikir kritis siswa. Selain itu, bahan ajar yang kontekstual juga meningkatkan keterlibatan siswa dan membantu mengaitkan materi pembelajaran dengan kehidupan nyata. Dalam konteks Sumatera Selatan, pemanfaatan potensi budaya lokal seperti tradisi, lingkungan sungai, dan sistem sosial masyarakat terbukti relevan sebagai sumber belajar. Meskipun demikian, pemanfaatan kearifan lokal dalam bahan ajar masih belum optimal di sebagian sekolah. Oleh karena itu, pengembangan bahan ajar berbasis budaya dan kearifan lokal perlu terus ditingkatkan sebagai strategi pembelajaran yang efektif dan kontekstual untuk meningkatkan literasi siswa sekolah dasar.